Evaluación de la eficiencia de un prototipo de humedal artificial de flujo subsuperficial para el tratamiento de aguas residuales domésticas provenientes de un pozo séptico (2022)
In this research work, the parameterization, construction and commissioning of an artificial wetland were carried out. In order to treat domestic wastewater from septic tanks. Since, the poor management of this domestic waste represents a sanitary and microbiological risk for rural communities that do not have a sewage system. According to the WHO, this represents a risk to public health and, accord ing to the FAO, the threat of crosscontamination to food increases, putting the food safety of these populations at risk. Therefore, this type of lowcost and easy families in rural atoimplement system turns out to be a viable alternative for low reas of the department of Boyacá. Since it allows them to pre-- income treat wastewater before being disposed of in tributaries or fertile cultivable soils. The results of this work demonstrate this. Since, the values for the physicochemical parameters such as BO D5, COD, TSS and real color are better than those allowed by resolution 631 of 2015. Additionally, the microbiological analysis shows an efficiency of 99.99% in the elimination of pathogenic microorganisms when carrying out the artificial wetland treatment .